Digital podcast: perceptions and attitudes among students at the Centre for Foundation Studies, IIUM - Ismail, Nur Farrah Syazwanie; Aling, Noor Asiah; Md Zahir, Mohd Syauqi; Saidin, Nurhafizah; Hassan, Suraya; Mohd Bashah, Bahirah (Asian Scholars Network, 2025)
Podcast-based learning which combines technology into the teaching and learning process has deviated from conventional methods and encourages a narrative approach to teaching, thus revolutionizing education. With this cutting-edge medium, students can interact with their learning materials at any time and from any location by leveraging the ease of use and accessibility of digital audio platforms. Podcasts grant information through storytelling, which makes learning more meaningful, interactive and engaging. Podcasts also support a variety of teaching and learning styles and enhance students’ comprehension. This study aims to investigate the impact of using Digital Podcast on the students’ perceptions and attitudes toward the course Understanding Islam 1 at the Centre for Foundation Studies, IIUM. This podcast incorporates online audio storytelling, which is designed to highlight essential classroom teaching and learning characteristics like creativity and reflection towards the course. A quantitative research approach was used to gather data through questionnaires comprising 13 items, examining students’ perceptions and attitudes. The data were then recorded in SPSS and analyzed using descriptive statistics. Additionally, interviews were conducted with selected students to further assess students’ perceptions and attitudes. The findings indicate that the Digital Podcast received positive perceptions among students, who expressed interest and comfort with podcast-based learning as a supplementary material in the course. They were reported to be more open and motivated to continue learning through podcasts in the future. Overall, it is obvious that using technology in audio podcasts has improved the students’ learning and given teachers the courage to abandon the antiquated model of traditional education.